Spray Dried Indapamide Microparticles For Controlled Release A Novel Approach - GOWDA D.V; KHAN M.S; NAGENDRA R (International Journal of Pharma and Bio Sciences, 2010)
The aim of the present study was to prepare and evaluate microparticles of Indapamide using blend of HPMC and Ethyl Cellulose by Spray drying technique for controlled release. Sieve analysis data indicated that the prepared microparticles were in the ranges of 265 µm to 187µm. The angle of repose, % Carr’s index and tapped density were well within the limit, indicating reasonable good flow potential for the prepared microparticles. SEM photographs and calculated sphericity factor confirms the prepared formulations are spherical in nature. DSC studies and FT-IR spectra showed that the encapsulated drug was stable in the prepared formulations. The prepared formulations were analyzed quantitatively for the amount of encapsulated drug. From the drug loading, encapsulation efficiency and in vitro drug release data, F6 was selected as optimized formulation. The optimum formulation F6 shows the drug release of 90.56 % up to 24 h and having drug loading and encapsulation efficiency of 66.82 ±0.27 % and 96.36 ±0.19 % respectively. It was also observed that, there was no significant release of drug at gastric pH. The release kinetics for all the formulations indicated that drug release followed non-Fickian diffusion. The optimized formulation was subjected for stability studies